PENGELOLAAN KEUANGAN KELUARGA DI MASA PANDEMI COVID 19 - Dina Khairuna Siregar; Azis Kurniawan; Ajwar Subhi; Megawati Megawati; Yanti Yanti (Gapenas Publisher, 2021)
The Covid 19 pandemic that occurred in 2020 impacts all areas of life, especially in the economy. The restriction of community activities causes a decrease in income that the government, business sector, and the community is not only felt by the government. This activity aims to increase the knowledge and ability of homemakers in managing family finances in the covid 19 pandemic period where many families' income decreases so that a mother as a financial manager must have knowledge and skills in family financial management. This activity was carried out at the Cisitu Village Office, attended by 20 participants consisting of homemakers and RT RW Cisitu Village. This activity went smoothly. The method of this service activity uses counseling and discussion methods. This activity shows that participants better know how to manage family finances by making household budgets, making spending priorities so that the income earned every month can meet all needs to avoid debt and start saving.